18 1/2 [videorecording (DVD)] - Moya, Daniel; Fitzgerald, Willa; Magaro, John, 1983-; Curtis-Hall, Vondie; Curtin, Catherine; Kind, Richard; Jones, Sullivan (Narrator); Schneider, Elle, 1985-; Guerra, Luis, 1975- (MVD Visual, 2024)
In January 1974, amid the Watergate scandal, White House transcriber Connie Lashley obtains a tape of Richard Nixon erasing the infamous 18 1/2-minute gap from his tapes. She travels to the isolated Chesapeake Bay town of St. Michaels to leak the tape to reporter Paul Marrow. As they struggle to find a working tape player, they realize they are not the only ones searching for the tape, as dark forces close in on them.